PENGARUH CORPORATE SOCIAL RESPONSIBILITY DESCLOSURE TERHADAP EARNING RESPONSE COEFFICIENT PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERCATAT DI BURSA EFEK INDONESIA - Paulus Tangke; Randhy (PROGRESS, 2014)
The objective of this study is to investigate the implementation of Corporate Social Responsibility Desclosure and to examine the influence of social responsibility disclosure ( CSR ) to the company's earnings response coefficient ( ERC ) in the Food and Beverage companies listed in Indonesia Stock Exchange . The results of the analysis carried out showed that between social responsibility disclosure ( CSRI ) with earnings response coefficients are positively affected . Where more and more social responsibility disclosure it will increase earnings response coefficients . The results of the analysis between social responsibility disclosure in earnings response coefficients significant influence and real. Where the higher the social responsibility disclosure significantly affect the earnings response coefficients . Thus the hypothesis is proven .